Anomalous Lingula Like Process In The Right Lung With Associated Anomalies : A Case Report - Nurzarina Binti Abdul Rahman; Srijit Das; Farihah Haji Suhaimi; Azian Abd Latiff; Faizah Othman (Japan International Cultural Exchange Foundation, 2024)
Objective: To study the morphological features of a cadaveric right lung exhibiting abnormal curvatures and notches along its anterior border. Materials and methods: The anterior border of right lung of a 55-year-old male cadaver was studied for the presence of abnormal curvatures and notches. Morphometric measurements were taken and the specimen was photographed. Results: The anterior border of the right lung showed the presence of convex curvature on the upper aspect, which extended 14 cm vertically and projected 2 cm outwards to the usual anterior border. Another notch was observed below this curvature, thereby leading to another projection anteriorly, which looked similar to the lingula of the left lung. On the inferior border, a notch was observed to be at a distant of 4 cm from the lower end of the anterior border. Thus, the anterior border exhibited notches and curvatures instead of being straight. The horizontal fissure was incomplete on its anterior aspect, whereas the oblique fissure was complete. Conclusion: Topograhical anatomy of the lung at its borders are important for academic and surgical purpose. Presence of anomalous fissures, lobes, notches and curvatures may result in erroneous interpretation of routine skiagrams.